Effect of steel fiber on the mechanical properties of oil palm shell lightweight concrete - Shafigh, Payam; Mahmud, Hilmi; Jumaat, Mohd Zamin (Elsevier, 2011)
This paper reports the results of a study conducted to investigate the effect of low volume content of steel fiber on the slump, density, compressive strength under different curing conditions, splitting tensile strength, flexural strength and modulus of elasticity of a grade 35 oil palm shell (OPS) lightweight concrete mixture. The results indicate that an increase in steel fiber decreased the workability and increased the density. All the mechanical properties except the modulus of elasticity (E) improved significantly. The 28. day compressive strength of steel fiber OPS lightweight concrete in continuously moist curing was in the range of 41-45. MPa. The splitting tensile/compressive and the flexural/compressive strength ratio for plain OPS concrete are comparable with artificial lightweight aggregate. The (E) value measured in this study was about 15.5. GPa on average for all mixes, which is higher than previous studies and is in the range of normal weight concrete. Steel fiber can be used as an alternative material to reduce the sensitivity of OPS concrete in poor curing environments.